Ta’līm Mahārah al-Kalām: bayna al-Muwaqa’āt wa Hulūlihā - Alfisyahrina, Khuzaimah; Nisak, Rahmatun; Astuti, Fuji; Muslimah, Hidayatil (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2024)
Purpose- This study aims to find out the obstacles that students face in learning Arabic Language specially in speaking skill and to find out the efforts made by teachers to overcome them and also to find the solution to solve these problems. Design/Methodology/Approach- This Study used a descriptive analysis using research instruments in the form of interviews and observations. The data will be analyzed qualitatively. The validity of the data was tested by using the triangulation technique. The data were obtained through field research. Findings- Based on the results of the research that some of the students’ obstacles in speaking Arabic are: lack of vocabulary, little practice with their friends, fear of making mistakes in speaking, teachers are used to speaking Bahasa either with other teachers or with students, and language organization runs ineffectively, as for some of the solutions that teachers need to do are establishing language environment, implementing vocabulary learning in the morning every day, punishing students who don’t speak Arabic, requiring students to memorize vocabulary, using some learning media such as movies to attract students’ interest in learning, enforcing language obligations for dormitory teachers especially when with students, provide language facilities such as: Arabic mading etc, special training for members of language section of the language section of the organization. Research Limitation/Implications- The limitation of the research in this s tudy focus on the problem of speaking skill in student’s daily activity at Ma’had Al-Furqan Bambi Class VIII.